DAMPAK PIJAT BAYI MENGGUNAKAN MINYAK AROMATERAPI LAVENDER TERHADAP KUALITAS TIDUR BAYI USIA 6-9 BULAN - Sara Herlina; Siti Qomariah; Wiwi Sartika (LPPM Universitas Abdurrab, 2025)
Introduction Infants frequently experience sleep disturbances, such as sleeping for less than 8 hours and waking up three times during the night, each time staying awake for more than an hour. One approach to address sleep problems in infants is baby massage. Baby massage is a non-pharmacological method used to manage sleep disorders in infants. An effective stimulus to help infants sleep more soundly is massage combined with the use of aromatherapy. Aromatherapy works by dispersing fragrant molecules into the air and stimulating the central nervous system, which helps the infant fall asleep more easily. Objective This study aims to determine the effect of baby massage using lavender aromatherapy oil on the sleep quality of infants aged 6–9 months. Method This research employed a quasi-experimental method with a one-group pre-test and post-test design. The sample consisted of 30 infants aged 6–9 months who were experiencing sleep disturbances. Data were collected through observation and questionnaires that had been tested for validity and reliability. Results The results showed that baby massage using lavender aromatherapy oil in infants aged 6–9 months had a significant effect on improving sleep quality, with a p-value of 0.000. Conclusion It can be concluded that baby massage using lavender aromatherapy oil in infants aged 6–9 months positively affects the quality of infant sleep